ANALISIS KEPUTUSAN MAHASISWA DALAM MENGGUNAKAN QRIS SEBAGAI ALAT PEMBAYARAN NON TUNAI (STUDI PADA MAHASISWA UIN RADEN MAS SAID SURAKARTA) - Palupi, Caecilia Chendi; Setiawan, Agus (JURNAL ILMIAH EDUNOMIKA, 2025)
QRIS is an innovation in a non-cash payment system developed by Bank Indonesia to facilitate digital transactions quickly, safely, and efficiently. Its use is increasingly being chosen, especially among students, because it is in line with a practical and fully digital lifestyle. This study aims to analyze and determine the effect of perceived benefits, ease of use, perceived risk, and trust on the decision to use QRIS on students at UIN Raden Mas Said Surakarta simultaneously and partially. This study adopted a descriptive quantitative method with a purposive sampling technique involving 400 active students of UIN Raden Mas Said Surakarta who have experience or are familiar with the use of QRIS. Data analysis using the Partial Least Square (PLS) approach which includes model testing through the Outer Model, Inner Model, and hypothesis testing based on t-statistic values ​​and probability. The results of the study showed that Perceived benefits, perceived ease of use, perceived risk and trust simultaneously and partially had a positive and significant effect on the decision to use QRIS on students of UIN Raden Mas Said Surakarta.